Aqueous singlet oxygen reaction kinetics of furfuryl alcohol: effect of temperature, pH, and salt content. Issue 4 (28th February 2017) - Appiani, Elena; Ossola, Rachele; Latch, Douglas E.; Erickson, Paul R.; McNeill, Kristopher
Abstract : The rate constant for the reaction between furfuryl alcohol (FFA) and singlet oxygen ( 1 O2 ) in aqueous solution was measured as a function of temperature, pH and salt content employing both steady-state photolysis ( β value determination) and time-resolved singlet oxygen phosphorescence methods. Abstract : The rate constant for the reaction between furfuryl alcohol (FFA) and singlet oxygen ( 1 O2 ) in aqueous solution was measured as a function of temperature, pH and salt content employing both steady-state photolysis ( β value determination) and time-resolved singlet oxygen phosphorescence methods. The latter provided more precise and reproducible data. The reaction rate constant, k rxn, FFA, had a relatively small temperature dependence, no pH dependence and showed a small increase in the presence of high salt concentrations (+19% with 1 M NaCl). A critical review of the available literature suggested that the widely used value of 1.2 × 10 8 M −1 s −1 is likely overestimated. Therefore, we recommend the use of 1.00 × 10 8 M −1 s −1 for reactions performed in low ionic strength aqueous solutions (freshwater) at 22 °C. Furthermore, corrections are provided that should be applied when working at higher or lower temperatures, and/or at high salt concentrations (seawater).